From transmission to transaction: toward network models for effective health communication in Nigeria (2012)
The paper examines health communication as an evolving process from linear transmission to transactional discourse, a parpdigm shift for the attainment of meaningful, understandable and effective health knowledge acquisition in Nigeria. This holistic approach of information dissemination among people with diverse socioeconomic, demographic and cultural background addresses the complexity of human communication. The interest in network models, including Agency Health Transaction (AHT) and Convergence Models is in their nonlinear nature, which permits mutual negotiation and understanding of health messages among discussants. Accordingly, agents of communication can choose, negotiate and redefine norms based on active reasoning and strategizing. The position of this paper is therefore that the utilization of network models could lead to a relational perspective of effective health communication. This approach has implications for sustainable health maintenance and development in Nigeria and across sub-Saharan African regions.